Implementasi Pembelajaran Mendalam Dalam Menyusun Soal Berbasis Tes Kemampuan Akademik - Zaenal Mutaqin; Zulfah Laila; Samsijah, Samsijah; Atik Andriyani; Rais Ikhwanudin; Siti Umiyah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the implementation of in-depth learning and optimization efforts made by teachers in the process of compiling questions based on the Academic Ability Test (TKA). The research subjects were teachers at MIN 5 Boyolali, MIN 1 Boyolali, MTsN 2 Boyolali, MAN 2 Boyolali. The informants of this study were teachers. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the analysis show that the implementation of in-depth learning is carried out through four main activities, namely: (1) concept exploration, (2) contextual problem analysis, (3) reflection on understanding, and (4) designing reasoning-based test items. These four activities reflect the principle of deep learning which emphasizes in-depth understanding of the material. In addition, the study also found that teachers made optimization efforts through four complementary activities, namely: (1) increasing conceptual understanding, (2) strengthening context analysis, (3) deepening learning reflection, and (4) improving technical skills in compiling questions. Overall, the research results show that the implementation of in-depth learning and its optimization contribute significantly to improving the quality of TKA question preparation, although strengthening technical capabilities and further assistance are still needed to achieve more optimal results.